Fair Trade and the Role of Small Farmers and ARBs on Food Sovereignty in the Philippines - Ramos, Errol (Kasarinlan: Philippine Journal of Third World Studies; Vol 26 No 1-2 (2011): Food Sovereignty in Southeast Asia)
In light of global economic uncertainties, food shortages in many parts of the world, and climate change that greatly affects global agricultural production, how can small farmers and agrarian reform beneficiaries (ARBs), a large majority of which own one or less than one hectare of land, be truly the champions of food sovereignty and ultimately become the frontrunners of the new agricultural revolution in the Philippines? The answer would lie somehow on how small farmers and ARBs will be motivated to produce and how the government and the private sector will contribute effectively in arresting the decline of agricultural productivity. This paper explores how small farmers and ARBs must take the lead in agricultural development for the country to achieve food sovereignty and win in globalization.
Keywords: agriculture, agrarian reform, small farmers, globalization, trade